Arbuscular Mycorrhizal Fungi Enhance Biomass Growth, Mineral Content, and Antioxidant Activity in Tomato Plants under Drought Stress - Mohammad Zahangeer Alam; Tasrina Rabia Choudhury; M. A. U. Mridha (Journal of Food Quality)
Arbuscular mycorrhizal fungi (AMF) are symbiotically associated with crops. They increase biomass production, nutritional elements, and antioxidant activities in food and vegetable crops grown in soil under stress conditions. The present study focused on the effects of AMF (Acaulospora morrowiae, Paraglomus occultum, Funneliformis mosseae, Rhizophagus clarus, and Rhizophagus intraradices) on biomass growth and yield, contents of chlorophyll and carotenoids, activities of catalase (CAT) and ascorbate peroxidase (APX), and contents of hydrogen peroxide (H2O2), malondialdehyde (MDA), and minerals (Na, K, Ca, Mg, and Fe) in Unnayan, LT896, and Minto super tomato (Solanum lycopersicum L.) varieties grown in soil under drought stress (<10% moisture). The results showed that root length and shoot mass in plants treated with R. clarus and P. occultum were significantly higher than those of the control (non-AMF) in Minto super tomato. Compared to the control, the shoot’s dry weight and yield were enhanced by 28% and 20% with AMF-treated tomatoes. The CAT activity in P. occultum-treated plants was statistically higher than that of the control in Unnayan tomatoes. H2O2 content was detected higher in the control than R. clarus-treated LT896 tomatoes. In plants treated with A. morrowiae and R. clarus, APX activity was significantly higher than that of the control in the Unnayan tomatoes. CAT and APX activity increased by 42% and 66% in AMF-treated leaves of tomatoes compared to non-AMF. Treatment with AMF reduced the content of MDA and H2O2 (ROS) in the leaves of tomato plants by 50% and 2% compared to the control, respectively. Potassium (K), calcium (Ca), magnesium (Mg), and iron (Fe) of tomato fruits increased by 2%, 13%, 24%, and 37% with AMF treatment compared to the control. These results suggested that biomass growth, yield, photosynthetic pigments, antioxidant enzyme activity, and mineral contents could be enhanced by AMF in food crops grown under drought stress. It is concluded that AMF might be used for the development of AMF-enriched biofertilizers that will improve the nutritional quality of food crops grown under stress conditions.